PERANCANGAN SISTEM INFORMASI PERTANIAN BERBASIS WEB PADA DINAS PANGAN, TANAMAN PANGAN DAN HORTIKULTURA - Sobri Ansyah Putra; Suwarti Suwarti; Asparizal Asparizal (STMIK DUMAI, 2022)
This study aims to design an agricultural information system using the MySQL database programming language at the Riau Province food, agriculture and horticultural service by using the Design Unified Modeling Language (UML) modeling, one of the advantages of this system is the availability of fast information services. For agencies, this is the right way to share programs or services not only to employees but also to the public directly. The fact is that this information information system not only provides information online, but also with service value. It is hoped that the system that the authors develop This can be a place of service for all agencies, so that the design can be useful for the food, food plants and horticulture office of Riau province to develop the official website.Keywords: Agricultural Information Systems, WebsiteThis study aims to design an agricultural information system using the MySQL database programming language at the Riau Province food, agriculture and horticultural service by using the Design Unified Modeling Language (UML) modeling, one of the advantages of this system is the availability of fast information services. For agencies, this is the right way to share programs or services not only to employees but also to the public directly. The fact is that this information information system not only provides information online, but also with service value. It is hoped that the system that the authors develop This can be a place of service for all agencies, so that the design can be useful for the food, food plants and horticulture office of Riau province to develop the official website. Keywords: Agricultural Information Systems, Website